Increasing Growth Rate and Production of Bioactive Compounds Curcuminoid and Xanthorrhizol in Javanese Turmeric (Curcuma xanthorrhiza Roxb.) Rhizomes with Biso Zyme Application - Aziz, Sandra Arifin; Ridwan, Taopik; Batubara, Irmanida (Journal of Tropical Crop Science, 2018)
The bioactive compounds from Javanese turmeric (Curcuma xanthorrhiza Roxb.), curcuminoid and xanthorrhizol, have been used to treat human diseases. This research aims to study the Javanese turmeric growth, its curcuminoid and xanthorrhizol content using Biso Zyme with different concentration and interval spraying. Biso Zyme is is conjugated enzyme concentrate (CEC) produced by yeast extracts that can be applied to the plant to increase and improve plant yields. The treatments were arranged in a randomized block factorial design with three replications. The concentrations of Biso Zyme were 0.0, 0.1, and 0.05 %, with monthly spraying intervals at 1, 2, 3, 4 and 5 months after planting (MAP). The results showed that the highest leaf area index was 2.71 cm2g-1  followed by leaf area ratio which was 66.47 cm2.g-1 with 0.1% Biso Zyme application. Relative growth rate was 0.048 g.day-1while net assimilation rate was 0.00092 g.cm-2.day-1 without Biso Zyme application. The highest fresh and dry weight was those treated with 0.05% Biso Zyme applied at 4 to 5 MAP, i.e., 444.44 g and 68.72 g, respectively. The highest curcuminoid and xanthorrhizol contents were 0.435% and 1.505%, respectively, with 0.05% Biso Zyme spraying interval at 4 to 5 MAP, and 0.1%  Biso Zyme with sprayed at 1 to 5 MAP. Thin layer chromatography (TLC) analysis detected standard curcuminoid at Rf 0.23 and xanthorrhizol at Rf 0.66 with dichloromethane:chloroform eluents. Keywords: curcuminoid, Javanese turmeric, Leaf Area Index, organic fertilizer, xanthorrhizol